Toward a Civil Discourse : Rhetoric and Fundamentalism - Crowley, Sharon, 1943- (Book collections on Project MUSE., 2006)
"Sharon Crowley investigates the cultural factors that lead to the formation of beliefs, and how beliefs can develop into densely articulated systems and political activism. She underscores the urgency of developing a civil discourse, and through a review of historic rhetoric and its modern application, provides a foundation for such a discourse."--Jacket